1972
DOI: 10.1007/bf00036757
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome number and plant morphology in some ecotypes of Poa pratensis L.

Abstract: In a collection of Poa pratensis the variation in chromosome number and the relation between chromosome number and plant characters were studied . The material was collected at different places in the Netherlands . The number of chromosomes in the population varied from 33 to 92 . Plants with 56, 63, 70 and 77 chromosomes were in the majority. The occurrence of different chromosome numbers within almost all investigated plants led to the conclusion that aneusomaty is a rule in Poa pratensis . In the progeny of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 8 publications
(3 reference statements)
2
10
0
Order By: Relevance
“…However, it is likely that these values vary between individuals with each cultivar. These results support previous observations that Kentucky bluegrass has large variations in DNA content (Huff and Bara, 1993; Barcaccia et al, 1997) and in chromosome number (Speckmann and Vandijk, 1972). Interestingly, 91% of the genotypes tested fall in the range of 7 to 13 pg DNA/2C.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, it is likely that these values vary between individuals with each cultivar. These results support previous observations that Kentucky bluegrass has large variations in DNA content (Huff and Bara, 1993; Barcaccia et al, 1997) and in chromosome number (Speckmann and Vandijk, 1972). Interestingly, 91% of the genotypes tested fall in the range of 7 to 13 pg DNA/2C.…”
Section: Resultssupporting
confidence: 92%
“…However, some level of variation in chromosome number exists within each ploidy level, suggesting that some genotypes in our study may be aneuploids. The observed variation has been reported previously (Speckmann and Vandijk, 1972) and may be attributable to mitotic and meiotic aberrations (Porceddu et al, 2002).…”
Section: Resultssupporting
confidence: 83%
“…They continue to exist during the following generations and produce seeds. SPECKMANN and VAN DIJK (1972) studied Poa pratensis collected in various places in the Netherlands and found that the vast majority of plants were aneusomatic, the mean variation in chromosome numbers within the plants was 4. 7 and the maximum deviation was 9.…”
Section: )mentioning
confidence: 99%
“…P. pratensis L. (also known as Kentucky bluegrass and in the following denoted as P. pratensis) is an important cool season forage and turf grass that reproduces both sexually, by outcrossing and selfing, and apomictically. The contrasting modes of reproduction facilitate the high polyploidy levels and unusual chromosome numbers (x = 7, 2n = 28-147) observed in P. pratensis (Speckmann and van Dijk, 1972). P. pratensis shows persistence and resilience to cold and seasonal drought (Kanneganti and Kaffka, 1995) and good performance under frequent and close defoliation (Bryan et al, 2000;Durr et al, 2005).…”
Section: Introductionmentioning
confidence: 97%